KAJIAN ILMU MA’ANI KAIDAH INSYA’ THALABI AMR DALAM QS. AL-‘ALAQ AYAT 1 - emilda, puri (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2023)
This paper discusses the study of one of t he branches of balaghah science, namely ma'ani science which examines the first verse of Al-'Alaq, where the focus of the study of this paper uses the rules of ma'ani science, namely the rules of kalam insha' thalabi amr. The purpose of writing this paper is to provide knowledge to the reader about the insya' thalabi amr sentence, which has the meaning of news that requires the occurrence of something in the form of a command word which has a position as a rule of ma'ani science. Besides that, the discussion of this rule has various kinds based on something that has been determined through certain studies. Collecting data in this writing using literature study. The method used in this paper uses qualitative methods by taking literary sources such as balaghah science books, ulumul qur'an, related journals, interpretation of the Qur'an and so on using a descriptive analysis approach. The result of this writing is that in the letter Al-'Alaq verse 1 contains the rule insha' thalabi amr which in the content of the verse contains a command to read. Where the meaning of the order of reading is not narrowly but broadly